Triterpenes and Sterol from Tabernaemontana pandacaqui poir. - Ragasa, Consolacion Y.; Santos, Reyster O.; M. Cañete, Andrea Louise; S. Tan, Maria Carmen; Shen, Chien-Chang (Asian Journal of Chemistry, 2018)
Chemical investigation of the dichloromethane extract of Tabernaemontana pandacaqui Poir. flowers has led to the isolation of α-amyrin acetate (1), a mixture of α-amyrin acetate (1), lupeol acetate (2) and β-amyrin acetate (3) in about 4:2:1 ratio, α-amyrin fatty acid ester (4), a mixture of ursolic acid (5) and oleanolic acid (6) in about 1:1 ratio, and β-sitosterol (7). The structures of compounds 1-7 were identified by comparison of their NMR data with those reported in the literature.